Performance evaluation of a 5G-based hybrid visible light and radio frequency communication system - Peterle, Augusto Cesar Federici (2024)
The development of 5G is an ongoing process and annually release are published by 3GPP considering fundamental aspects such as network’s physical layer, numerology, bandwidth, modulation, among others. For new releases, a rapid prototyping is valuable for experimental demonstrations and proof-of-concepts. The usage of the Software-Defined Radio (SDR) technology is advantageous as it allows the implementation of modulation and demodulation procedures in software, enabling performance evaluations in various physical mediums, for instance both optical and Radio Frequency (RF). Besides the prototyping need, the growing congestion and limitation of the RF spectrum have led to exploring alternative communication mediums. Visible Light Communication (VLC) technology has emerged as a solution, utilizing an unlicensed optical spectrum without substantial communication competition. The rise in popularity of Light Emitting Diodes (LEDs) for residential and commercial lighting supports this idea, as LEDs can be controlled and employed as information transmitters and its low power consumption. To this aim, studies regarding optical communication and Orthogonal Frequency Division Multiplexing (OFDM), as well as an in-depth explanation of 5G New Radio (NR) numerol ogy were conducted. Therefore, a prototype was prepared and assembled for 5G NR signals generation for downlink via VLC, and for uplink via RF. The experimental results indicated that the coding techniques outlined by 5G NR integrate well with VLC, enabling the use of modulation levels up to 64-QAM. This outcome facilitated error-resistant communication for the transmitted data volume, showcasing a robust hybrid VLC/RF system capable of successfully supports relatively high data rates